Gain Control in L-Band Erbium-Doped Fiber Amplifier Incorporating Broadband Fiber Bragg Grating - Harun, Sulaiman Wadi; Tamchek, Nizam; Poopalan, Prabakaran; Ahmad, Harith (IOP Publishing, 2002)
Gain control in a two-stage long-wavelength (L-band) erbium-doped fiber amplifier (EDFA) is demonstrated. Two circulators and a broadband fiber Bragg grating (FBG) are used to route a wasted backward conventional band (C-band) amplified spontaneous emission (ASE) from the second stage and launch it back into the input end of the first stage. The amplifier gain is clamped at 16.5 dB with variation less than 0.2 dB and the dynamic range up to -7.5 dBm for the VOA loss of 4 dB. The clamped gain level can also be controlled from 15.0 to 22.9 dB by increasing the VOA loss from 0 to 32 dB without significant variation in the noise figure.